Analisis Penyebab Berlarutnya Sengketa Perbatasan Indonesia-Malaysia Di Pulau Sebatik Dalam Prespektif Hukum Internasional - Sahala Fransiskus marbun; Popy Ardian Ningsih Zega; Aisyah Nur Aini; Roma Ulina Sihotang; Rio Anggoro (PT. Pustaka Cendekia Publisher, 2025)
The boundary dispute between Indonesia and Malaysia on Sebatik Island is caused by differences in interpretation of the 1891 and 1915 Agreements between the Netherlands and England, which have not yet produced a final agreement. Indonesia adheres to the principle of Uti Possidetis Juris, while Malaysia considers the need for re-delimitation according to geographical conditions. This study aims to analyze the factors causing this dispute to drag on from an international legal perspective and to evaluate efforts to resolve it. The method used is qualitative research with a literature review approach, reviewing 16 national journals discussing the Sebatik Island border dispute. The results of the study show that although various diplomatic efforts have been made through the Joint Indonesia-Malaysia Boundary Committee (JIM) forum and the installation of new boundary pillars in 2019, there has been no binding agreement between the two countries. This conflict also has an impact on the economic dependence of the Sebatik community on Malaysia, which risks weakening Indonesia's sovereignty. Therefore, a more effective negotiation strategy is needed, including the possibility of international arbitration through the International Court of Justice (ICJ), as well as improving the welfare of border communities in order to strengthen Indonesia's territorial sovereignty.